(untitled) (Journal of Social Economics Research, 2021)
The emergence of financial technology (Fintech) has led to an increased need to promote efforts to boost the financial literacy of young professionals, as the financial decision-making process has become more challenging. The specific objectives of this study are to gauge the financial knowledge of young professionals and analyze their attitudes and behavior in regards to the use of Fintech for basic money management, financial planning and investment decisions. The study also aims to analyze the extent to which Fintech is used and its impact on financial literacy levels. The research methodology employs a dual approach. A quantitative study using a survey targets young professionals in the different occupational groups that constitute the Mauritian professional workforce. A regression model is developed to investigate the impact of Fintech usage and demographic factors on financial literacy. The findings reveal significant differences in financial knowledge, attitudes and behaviors attributable to various demographic factors. Furthermore, Fintech usage is limited to the traditional offerings while more innovative Fintech has relatively lower adoption rates. The study has uncovered the positive impact of Fintech usage on financial literacy, opening avenues for rethinking the content and scope of traditional financial education programs.